(untitled) (Research, Society and Development, 2021)
Objective: to build and validate educational technology to guide Primary Health Care health professionals in the care of cardiorespiratory arrest. Method: this is a methodological research developed in three phases: literature review; elaboration of illustrations, layout, design and texts and apparent and content validation, the latter was carried out between December / 2019 and January / 2020. The content validation counted on seven experts on the subject and tested the Content Validity Index, considering valid values ​​equal to or greater than 0.80. In addition, the validation process took place in two evaluation rounds: the first consisted of evaluating the educational material related to the management of cardiopulmonary resuscitation and the second round was the evaluation of the material referring to advanced life support medications, obtaining a total of 14 reviews. Results: The educational technology was entitled “Educational technology for the care of patients in Cardiopulmonary Arrest in Primary Health Care”. The professionals assigned a global Content Validity Index of 0.89, which demonstrates that educational technology was considered validated in terms of content and appearance. Conclusion: The technology proved to be valid and reliable for the use of health professionals in the care of patients in cardiac arrest in Basic Health Units with a satisfactory global Content Validity Index.